Morphometric Characteristics and Condition Factors of Green Shells (Perna viridis) in The Waters of Randusanga Kulon Brebes, Central Java - Faizah, Farkhah Nur; Imlani, Ainulyakin Hasan; Sanjayasari, Dyahruri (Fakultas Perikanan dan Ilmu Kelautan, 2024)
ABSTRACT Green mussel (Perna viridis) is one of the species of bivalve class that is commonly found in the waters of Randusanga kulon, Brebes, thus becoming one of the sources of income for the people in the area. The purpose of this study was to determine the morphometric condition of green mussels based on length and weight and condition factors of green mussels in Randusanga kulon waters. Was used in this study regression analysis quantitative method. The results of the study showed the green mussel morphometry average length was 11.78 cm ± 1.51 with average weight was 90.749 gr ± 24.1. The value of b from the length-weight relationship of green mussels is 0.0045, meaning that the value of b <3 is allometrically negative, namely the growth of length faster than its weight. The condition factor of green mussels was 1.02, which is classified as having a good proportions and indicates a decent water condition. Keywords: Condition Factors, Green Mussels, Morphometry,Growth, Randusanga Kulon ABSTRAK Kerang hijau (Perna viridis) merupakan salah satu spesies dari kelas bivalvia yang banyak ditemukan di perairan Randusanga kulon, Brebes, sehingga menjadi salah satu sumber pendapatan masyarakat di daerah tersebut. Tujuan dari penelitian ini adalah untuk mengetahui kondisi morfometrik kerang hijau berdasarkan panjang dan berat serta faktor kondisi kerang hijau di perairan Randusanga kulon. Metode yang digunakan dalam penelitian ini adalah metode kuantitatif analisis regresi. Hasil penelitian menunjukkan morfometri kerang hijau panjang rata-rata adalah 11,78 cm ± 1,51 dengan berat rata-rata 90,749 gr ± 24,1. Nilai b dari hubungan panjang-berat kerang hijau adalah 0,0045, artinya nilai b < 3 bersifat allometrik negatif, yaitu pertumbuhan panjang lebih cepat dibandingkan dengan beratnya. Faktor kondisi kerang hijau sebesar 1,02 yang tergolong memiliki proporsi yang baik dan mengindikasikan kondisi perairan yang layak. Kata Kunci: Faktor Kondisi ,Kerang Hijau, Morfometri, Pertumbuhan, Randusanga Kulon